2009
DOI: 10.1149/1.3078405
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration Kinetics of PEG, PPG, and a Triblock Copolymer by SPS during Copper Electroplating

Abstract: Three copper-plating suppressors are examined in three-additive baths: a polyethylene glycol ͑PEG͒, a polypropylene glycol ͑PPG͒, and a triblock copolymer of the two. Bis͑3-sulfopropyl͒-disulfide ͑SPS͒ is found to transition each to a state of nonsuppression, i.e., accelerate each, at a rate dependent on the suppressor molecule, the SPS concentration, and, to a lesser extent, the suppressor concentration. Using a planar microscale working electrode ͑d = 100 m͒, the kinetic currents of the plating reactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
79
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 32 publications
6
79
1
Order By: Relevance
“…That meant the more PO segments in the molecules would lead to the stronger suppression strength of the suppressors. This result was in line with that observed by West et al 21 Using the optimized Cl − concentrations for each suppressor, GMs were performed for evaluating the filling performances of the plating baths containing suppressors at a low concentration of 20 ppm suppressors, as shown in Fig. 7.…”
Section: The First Groupsupporting
confidence: 87%
“…That meant the more PO segments in the molecules would lead to the stronger suppression strength of the suppressors. This result was in line with that observed by West et al 21 Using the optimized Cl − concentrations for each suppressor, GMs were performed for evaluating the filling performances of the plating baths containing suppressors at a low concentration of 20 ppm suppressors, as shown in Fig. 7.…”
Section: The First Groupsupporting
confidence: 87%
“…To emulate the latter condition, a microfluidic device was used to observe in-situ changes on the electrode structure: the electrolyte flow is a medium to induce shear stress on the electrode surface. [10][11][12] This shear stress was correlated with the shear stress observed on the electrode surface during the flexing of the battery. Learning from these studies, we demonstrated a flexible battery electrode based on a mesh embedded architecture.…”
mentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The main mechanism of superfilling is the local promotion of Cu deposition at the bottom of the features. This controlled deposition rate according to the location within the feature, is enabled by the adsorption of different types of organic additives, and the changes in their surface coverage.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In contrast, various polyethers in combination with chloride ions are employed as the suppressor, and polyethylene glycol (PEG), polypropylene glycol (PPG), and their block copolymers are the typical suppressors. [1][2][3][4][5][6][7][8][9][10][11][12] The superfilling mechanism has been understood based on the Curvature Enhanced Accelerator Coverage (CEAC) model. [13][14][15] This model emphasized the accumulation of accelerators, through area reduction at the bottom corners of filling features, as the electrodeposition progresses.…”
mentioning
confidence: 99%